Gabapentin Produces Dose-Dependent Antinociception in the Orofacial Formalin Test in the Rat. Issue 3 (1st May 2002) - Grabow, Theodore S.; Dougherty, Patrick M.
Abstract : Background and Objectives: High neuraxial drug infusion has been advocated for the treatment of intractable cranial and facial pain in humans. Currently, parallel animal models have not been characterized to support this methodology. We combined an accepted animal model of pain of cranial origin with a novel technique of cervico-medullary drug delivery to determine the antinociceptive potential of gabapentin. Gabapentin was chosen because of its reported efficacy in a wide array of complex cranial pain syndromes. Methods: Male Wistar rats were implanted with intrathecal catheters that were advanced cephalad through a lumbar guide cannula to terminate in the high cervical spinal cord (C1-C4). Antinociception was assessed by the orofacial formalin test. Vehicle or gabapentin (3, 10, 30, 100 μg) was injected intrathecally followed 10 minutes later by injection of 2.5% formalin solution into the vibrissal pad. Motor assessment was evaluated in a separate group of animals. Results: Intrathecal gabapentin (10, 30, 100 μg) produced a dose-dependent decrease in the second phase of the behavioral response to formalin ( P < .05). First-phase responses were unaffected by all doses of gabapentin. The ED50 (95% confidence limit) value for the second phase was 8.27 μg (3.50 to 14.5). No overt motor dysfunction or behavioral impairment was observed. Conclusions: Gabapentin produced dose-dependent antinociception in the second phase of the orofacial formalin test in the rat after injection into the cervico-medullary cerebrospinal fluid. This animal model may be useful to assess analgesics designed for parallel clinical application in humans for the treatment of intractable head and neck pain that is refractory to conventional modalities.